TPACK-Driven Digital Pedagogy in Islamic Elementary Education: Enhancing Learning Outcomes and Motivation in Aqidah Akhlak - Gina Fauziyah; Jamali Sahrodi; Abdul Aziz (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study aims to examine the effectiveness of TPACK-driven digital pedagogy in enhancing learning outcomes and learning motivation in Aqidah Akhlak among Islamic elementary students. Using a quantitative quasi-experimental pretest-posttest control-group design, the study involved fifth-grade students at SDIT Harapan Ummah Karawang. The experimental group received TPACK-based instruction, whereas the control group experienced conventional teaching. Data were collected through validated learning outcome tests and learning motivation questionnaires and analyzed using normality, homogeneity, and independent samples t-tests. The findings revealed that students exposed to TPACK-driven digital pedagogy achieved significantly higher learning outcomes and stronger learning motivation than those in conventional classrooms. These results indicate that integrating technology, pedagogy, and content knowledge creates more engaging, meaningful, and effective Aqidah Akhlak learning. The originality of this study lies in providing empirical evidence from Islamic elementary education, an underexplored context within TPACK research. Furthermore, the study extends existing scholarship by demonstrating that TPACK enhances both cognitive achievement and affective engagement simultaneously, offering practical guidance for teachers, schools, curriculum developers, and policymakers seeking sustainable digital transformation in Islamic Religious Education through pedagogically meaningful technology integration initiatives.